Single-Domain Antibodies: Biology, Engineering and Emerging Applications - Kevin A. Henry (Frontiers Research Topics, 2018)
Single-domain antibodies (sdAbs) represent the minimal antigen binding-competent form of the immunoglobulin domain and have unique properties and applications. SdAbs are naturally produced as the variable domains of the heavy chain-only antibodies of camelid ruminants and cartilaginous fishes, but can also be engineered synthetically from autonomous human or mouse VH or VL domains. The scope of this research topic and associated e-book covers current understanding and new developments in (i) the biology, immunology and immunogenetics of sdAbs in camelids and cartilaginous fishes, (ii) strategies for sdAb discovery, (iii) protein engineering approaches to increase the solubility, stability and antigen-binding affinity of sdAbs and (iv) specialized applications of sdAbs in areas such diagnostics, imaging and therapeutics.